The influence of carotid plaque on carotid artery stiffness indicators in hypertensive patients with and without accompanying type 2 diabetes - V. V. Syvolap; A. O. Bohun (Zaporozhye State Medical University, 2024)
Aim. To compare the elastic properties of the common carotid arteries (CCA) in patients with stage II hypertension (HTN) depending on the presence of diabetes mellitus (DM) and atherosclerotic plaque (ASP) <50 % of carotid arteries (CA). Materials and methods. The study included 80 patients with stage II HTN, 43 of them without type 2 DM, 37 with type 2 DM, average age - 57.7, 55.3 % men. Basic anthropometric data, laboratory indicators of lipid and carbohydrate metabolism, creatinine, data of daily blood pressure monitoring, echocardiography, intima-media thickness, local stiffness indicators: artery diameter, distensibility, the distensibility coefficient (DC), and compliance coefficient (CC), stiffness indices α, β, local pulse wave velocity (PWV), pressure and augmentation index (using radiofrequency-based technologies) were studied. Statistical analysis was performed; the probability of differences is at the level of p < 0.05. Results. The prevalence of ASP in the carotid basin in the group of patients with HTN without DM was 51.1 %, with DM - 54.0 % (p = 0.79). While comparing the elastic properties of CCA of patients without ASP, no reliable similarities were found in the studied indicators. In patients with HTN, accompanying type 2 DM with ASP, the diameter of the CCA was significantly larger by 11.8 % (p = 0.03), and the CC was also higher by 23.6 % (p = 0.049) than in patients with HTN without DM. In patients with HTN with and without DM the limit levels for the intima-media thickness of the left CCA associated with the presence of atheroma were determined, however, the comparison of the areas under the ROC curves did not reveal a statistical difference in the cut-off values in the studied groups (р = 0.681). Conclusions. A feature of CCA remodeling in HTN patients with DM at the stage of ASP presence should be considered a more substantial increase in the diameter of the CCA with preservation of the distensibility of the plaque-free vascular wall. The addition of a second factor (DM) to one risk factor (HTN) is not accompanied by a further statistically significant increase in IMT as a mandatory prerequisite for the appearance of ASP.